Prognostic value of p14ARF expression in diffuse large B cell lymphoma - М. V. Sarpova; Е. V. Vaneeva; D. A. Diakonov; V. A. Rosin; S. V. Samarina (Сибирский научный медицинский журнал, 2024)
The p14ARF-Hdm2-p53 signaling pathway targets tumor growth suppression, inhibits clonal proliferation, and maintains genome stability. It is inactivated in most human malignancies. The p14ARF protein is one of the main participants in the cascade. The aim of the study was to determine the prognostic value of the number of p14ARF-expressing tumor cells in biopsies of patients with diffuse large B cell lymphoma (DLBCL). Material and methods. The formalin-fixed paraffin embedded samples of tumor tissue of 104 patients with newly diagnosed DLBCL were included to the study. The relative number of cells expressing p14ARF was determined by immunohistochemical and morphometric methods. Differences in the content of p14ARF-positive tumor cells between groups of patients divided according to clinical and laboratory parameters were determined using the Mann–Whitney U test. Prediction of an unfavorable response to therapy was carried out using binary logistic regression with calculation of the odds ratio and 95 % confidence interval; variables were selected using Wald backward elimination method. The risk of an event occurring was calculated using Cox regression analysis. Results. The content of p14ARF-positive cells is higher in tumor biopsies of patients with high and high-intermediate risk according to the international prognostic index than in patients with low and lowintermediate risk. A relationship between an increase in the number of p14ARF-positive tumor cells, the absence of a complete response to first-line R-CHOP therapy, and an increased risk of death in patients with DLBCL has been established. Conclusions. The studied marker p14ARF can be used as an additional morphological predictor of the unfavorable course of DLBCL.